Endoscopic removal of ureteral stones - Castillo, Solon; Romero, Manuel (Revista Universidad de Guayaquil, 1988)
The endoscopic treatment of ureteral stones has evolved significantly, having broad indications and an indisputable usefulness that makes it especially advisable. This is a prospective study of endoscopic treatment in 12 patients with single or multiple ureteral lithiasis, in whom the Zeiss Loop Probe was used.